THE PERCEPTION OF ACCOUNTING STUDENTS ON THE EFFECTIVENESS OF PRACTICUM SUBJECT - Yatnanta Ramadhana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The study aims to know the perceptions of accounting students of Brawijaya University regarding the effectiveness of practicum subjects. The study was done to 60 respondents of accouting students that are being or have been studied practicum subjects. There are 5 practicum subjects provided by Accounting Departement, as follows: accounting practicum subject, taxation practicum subject, accounting information system practicum subject, managerial accounting practicum subject, and auditing practicum subject. The content of questionnaire was taken from the practicum subjects itself. The questionnaire is using Likert scale as the approach. The study is using quantitative descriptive approach and validity also reliability test. The effectiveness measured using 3,5 as the limitation of value in the basic calculation of effectiveness. According to the descriptive quantitative approach, there were 3 of 5 subjects that are effective. However, the taxation practicum subject and managerial accounting subject are still below the limit value of effectiveness. Keyword : accounting practicum subject, taxation practicum subject, accounting information system practicum subject, managerial accounting practicum subject, auditing practicum subject, effectiveness